DAMPAK PENGUMUMAN HASIL PEMILIHAN UMUM 2024 PADA EMITEN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Naila Qisthi; Rusma Nailiah; Fahmi Rizani (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aimed to analyze the differences in the average abnormal return, trading volume activity, security return variability, and market capitalization in LQ45 stocks before and after the announcement of the 2024 general election results. The population in this study was stocks included in the LQ45 stock index listed on the Indonesia Stock Exchange for the period February - July 2024. The data used in this study were secondary data in the form of daily stock prices, The research period during 10 stock trading days, consisting of 5 days before and 5 days after the event. The analysis technique used was a paired sample t-test and Wilcoxon signed ranks test. The results of this study proved that there were differences before and after the announcement of the 2024 general election results on the average trading volume activity, in contrast to the abnormal return, security return variability, and market capitalization variables, where there was no difference in the average before and after the announcement of the 2024 general election results.